Clean Sweep: Informed Trading through Intermarket Sweep Orders - Chakravarty, Sugato; Jain, Pankaj; Upson, James; Wood, Robert (Journal of Financial and Quantitative Analysis, 2012)
Abstract An intermarket sweep order (ISO) is a limit order that automatically executes in a designated market center even if another market center is publishing a better quotation. An investor submitting an ISO must satisfy order protection rules by concurrently submitting orders to the markets with better prices. We find that ISOs represent 46% of trades and 41% of volume in our sample. ISO trades have a significantly larger information share despite their small trade size relative to non-ISO trades. Post trade return analysis suggests that informed institutions are the main users of ISO trades.